Strategi Pemetaan Kualitas Pendidikan Sekolah Dasar di Dinas Pendidikan Kota Yogyakarta melalui Kebijakan Asesmen Standarisasi Pendidikan Daerah (ASPD) - Rizki, Amilia (Fakultas Ilmu Pendidikan, 2025)
This study aims to describe ASPD as a quality mapping strategy for elementary school education in Yogyakarta City using educational policy theory and policy strategies. This study uses a descriptive qualitative approach with data collection techniques, namely observation, interviews, and document studies. The research subjects were the Head of Elementary School Curriculum at the Yogyakarta City Education and Culture Office, school principals, and ASPD coordinators. The data analysis technique used the interactive model of Miles, Huberman, and Saldana. The results of the study: (1) Planning ASPD objectives to develop student competencies, the basis for mapping educational quality, improving learning, monitoring quality developments and gaps, and one component of calculating scores in the PPDB selection. (2) The implementation of ASPD is carried out in an organized, interpreted, and applied manner in accordance with the POS ASPD. a) Impact: increasing student learning motivation, improving learning quality, becoming a reference model for assessment, giving rise to pros and cons of policies, and becoming a challenge for schools. (3) ASPD results are managed to provide interventions to teachers, see the development of learning quality, and guidelines for making subsequent policies. a) The aspect of mapping the quality of education through ASPD is PISA (reading literacy, numeracy literacy, and scientific literacy) which is guided by the National Education Standards (SNP).